Hydrogel with controllable and enhanced mechanical properties as well as preparation and application of hydrogel

By using piezoelectric wire hydrogel prepared with glycine-polyvinyl alcohol and methacrylylated wire, combined with ultraviolet light pre-crosslinking and ultrasonic treatment, the problem that existing hydrogel materials cannot dynamically adapt to the osteocartilage repair stage is solved, dynamic enhancement of mechanical properties and biocompatibility, and the regeneration of osteocartilage tissue is achieved.

CN119708545AActive Publication Date: 2025-03-28ZHEJIANG UNIV

Patent Information

Application Number
CN202510214557.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-28
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

Existing hydrogel materials cannot dynamically adapt to the material mechanical needs of different repair stages after implanting osteocartilage tissue defects, and the biocompatibility and mechanical enhancement range are not suitable for osteocartilage repair.

Method used

The piezoelectric wire hydrogel with glycine-polyvinyl alcohol and methacryylated wire as the main components is used to achieve dynamic enhancement of mechanical properties and biocompatibility through ultraviolet light pre-crosslinking and ultrasonic treatment.

Benefits of technology

Dynamic enhancement of the mechanical properties of hydrogels is achieved, and the changes in mechanical strength can be controlled by the time of ultrasonic intervention, adapted to different stages of cartilage tissue repair, and improved biocompatibility and promoted the regeneration of osteocartilage tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708545A_ABST
    Figure CN119708545A_ABST
Patent Text Reader

Abstract

The invention provides hydrogel with controllable and enhanced mechanical properties and preparation and application thereof, the hydrogel mainly comprises glycine-polyvinyl alcohol and methylacryloylated fibroin, and glycine-polyvinyl alcohol crystal film powder and methylacryloylated fibroin are pre-crosslinked by ultraviolet light to obtain piezoelectric fibroin hydrogel. And performing ultrasonic treatment on the hydrogel to obtain the piezoelectric fibroin hydrogel with enhanced mechanical strength. Compared with a traditional organic piezoelectric material, the glycine-polyvinyl alcohol piezoelectric material used in the invention has a higher piezoelectric coefficient; the components of the methacrylated fibroin and the glycine-polyvinyl alcohol have good biocompatibility; the hydrogel can be used for treating cartilage defects, and the change of the mechanical strength of the hydrogel material can be regulated and controlled by applying external ultrasonic intervention time, sound intensity, frequency and the like, so that the mechanical strength of the hydrogel can dynamically adapt to different stages of repairing of movement system tissues including cartilage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of biomedical engineering and hydrogel manufacturing technology, and in particular to a silk hydrogel with controllably enhanced mechanical properties and the preparation and application thereof. Background Art

[0002] Osteoarthritis, as a degenerative disease, can lead to loss of mobility, severe pain, and easily induce other chronic diseases. The onset of osteoarthritis is usually caused by defects in cartilage tissue, and due to frequent stimulation of movement, it is difficult to recruit chondrocytes and easily induce inflammatory reactions; currently, cartilage defects are difficult to repair. Natural osteochondral tissue has the effect of generating bioelectric current in response to external stimuli. Current studies have shown that external electrical stimulation can promote the regeneration and differentiation of osteochondrocytes. The piezoelectric effect is a physical and chemical effect in which a material can sense external mechanical stimuli, such as pressing, stretching, electromagnetic waves, ultrasonic stimulation, etc., so that the internal molecules produce charge polarization, thereby forming a transient current. Materials with piezoelectric effect can make up for the functional loss of generating bioelectric signals in response to external stimuli caused by cartilage defects. Therefore, current studies have shown that piezoelectric materials can promote the regeneration of animal osteochondral defects.

[0003] The mechanical properties of the materials that promote cartilage defect regeneration in current research will remain stable after the materials are prepared and will not change further. However, the mechanical properties of the materials have an impact on the different stages of cartilage tissue repair. The development of osteochondrogenesis is the process of development from loose connective tissue to dense connective tissue. In this process, the mechanical properties of osteochondrogenesis gradually increase. It is difficult for existing materials to continue to maintain dynamic improvement in mechanical properties after implantation in the body, so it is difficult to adapt in time to the enhancement of mechanical properties of osteochondrogenesis.

[0004] At the same time, the inflammatory response and cell recruitment during osteochondral regeneration are also closely related to the mechanical properties of the material. Studies have shown that with the improvement of the mechanical strength of the implanted scaffold material, the polymerization of cell actin can be promoted, thereby activating the Piezo 1 pathway and leading to the aggravation of the inflammatory response. In addition, studies have also shown that the improvement of the mechanical strength of the implanted material will also promote the acetylation of intracellular tubulin, thereby promoting the migration and recruitment of cells at the defect. It can be seen that in the early inflammatory response period of osteochondral repair, the repair of the defect prefers a scaffold material with lower stiffness to reduce the local inflammatory response, while in the middle and late tissue repair period of osteochondral repair, the repair of the defect prefers a scaffold material with higher stiffness to promote cell recruitment and osteochondral regeneration. In the current research on the influence of material mechanics on inflammatory response and cartilage regeneration, it can be found that materials with a mechanical strength of the order of kPa are beneficial to reduce the occurrence of inflammatory response in the early stage of osteochondral regeneration; when the mechanical strength reaches the order of 10kPa, the material is more conducive to the expression of YAP protein and cell recruitment in the middle and late stages of osteochondral regeneration, thereby promoting cartilage tissue regeneration.

[0005] In the existing technology, a study has developed an inorganic piezoelectric material that responds to external force loading and promotes the enhancement of mechanical properties by incorporating it into hydrogel. In this study, a phenomenon based on the charge polarization inside the molecules of piezoelectric zinc oxide particles during external mechanical force loading was proposed, which was used to trigger the generation of free radicals inside the hydrogel and then promote the free radical chain reaction of molecular monomers. The piezoelectric effect was used to trigger the mechanical strength of the hydrogel to increase with external mechanical loading. However, in this study, high-frequency and long-term loading was required to induce the piezoelectric effect, and this mechanical loading method is difficult to be applied to the body of actual living animals. At the same time, the inorganic piezoelectric material incorporated in this study is also difficult to degrade in vivo. In addition, the range of variation in the mechanical strength of the materials studied in this article is also difficult to adapt to the different stages of cartilage repair.

[0006] In summary, the problems existing in the prior art mainly include the following: (1) The mechanical properties of existing hydrogel materials cannot dynamically adapt to the mechanical requirements of materials at different repair stages after being implanted into osteochondral tissue defects, and there is a lack of hydrogel materials with dynamically enhanced mechanical properties; (2) The existing mechanical property enhanced materials have poor biocompatibility, and the adjustable mechanical change range is not suitable for the repair of osteochondral tissue. There is a lack of materials with high biocompatibility and adaptability to the mechanics of osteochondral repair; (3) The mechanical strength of existing mechanical property enhanced materials cannot be accurately controlled by regulating the time of external intervention, and there is a lack of research on the specific correspondence between the mechanical strength of the material and the external loading time; (4) The external intervention methods and intervention conditions for the existing mechanical property dynamically enhanced materials to induce changes in the mechanical strength of the material are not suitable for in vivo tissue repair, and there is a lack of low-invasive and painless intervention methods to induce the enhancement of the mechanical properties of the material.

[0007] Since the repair process of osteochondral defects is a process that gradually increases the requirements for the mechanical properties of materials, and has corresponding requirements for the biocompatibility of the material itself, the range of mechanical enhancement, and the external intervention method that induces mechanical enhancement. Therefore, the tissue engineering repair of osteochondral materials has put forward a new demand for a piezoelectric scaffold material with controllable mechanical property enhancement. It is necessary to develop a hydrogel material with good biocompatibility, dynamic in situ enhancement in vivo, controllable mechanical strength enhancement, a way to induce mechanical enhancement, and external intervention that is beneficial to the repair of osteochondral tissues to effectively address the above deficiencies. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a hydrogel with controllable enhanced mechanical properties and a preparation method thereof, wherein the main components of the hydrogel are glycine-polyvinyl alcohol and methacrylylated silk fibroin, the glycine-polyvinyl alcohol crystal film powder and the methacrylylated silk fibroin are pre-crosslinked by ultraviolet light to obtain a piezoelectric silk fibroin hydrogel, and the hydrogel is subjected to ultrasonic treatment to obtain a piezoelectric silk fibroin hydrogel with enhanced mechanical strength. The glycine-polyvinyl alcohol piezoelectric film and powder used in the present invention have a higher piezoelectric coefficient than traditional organic piezoelectric materials; the methacrylylated silk fibroin and glycine-polyvinyl alcohol components have good biocompatibility; they can be used for the treatment of cartilage defects, and the change in the mechanical strength of the hydrogel material can be regulated by the time of applying external ultrasonic intervention, so that the mechanical strength of the hydrogel can dynamically adapt to different cartilage tissue repair stages.

[0009] On the one hand, the present invention provides a hydrogel with dynamically enhanced mechanical properties induced by piezoelectric effect, wherein the hydrogel comprises a piezoelectric component and a colloidal component, and is obtained by cross-linking; the piezoelectric component comprises any one or more of barium titanate (BaTiO3) and glycine-polyvinyl alcohol crystals, and the colloidal component comprises any one or more of methacryloyl silk fibroin (SilMA), methacryloyl gelatin (GelMA), and acrylamide (AM).

[0010] The piezoelectric effect refers to the phenomenon that the pressure, tension or waves applied to certain crystals or ceramic materials cause changes in the material's electric potential, which in turn causes the internal charge to rearrange and produce uneven charge distribution, thereby generating a potential difference and electric field strength at both ends of the material. Materials with piezoelectric effect can make up for the functional loss of generating bioelectric signals in response to external stimuli caused by cartilage defects. The mechanical properties of piezoelectric materials that promote cartilage defect regeneration in current research will remain stable after the material is prepared and will not change further. The hydrogel material provided by the present invention can induce dynamic enhancement of the mechanical properties of the hydrogel through the piezoelectric effect, and the mechanical strength enhancement is controllable, which can adapt to different stages of cartilage repair.

[0011] Furthermore, the piezoelectric component includes glycine-polyvinyl alcohol crystals, and the colloidal component includes methacrylylated silk.

[0012] At present, most of the piezoelectric materials used in the prior art have low piezoelectric coefficients and high costs. For example, polyvinylidene fluoride materials are relatively expensive, may be affected by strong oxidants under extreme conditions, and are difficult to process. Zinc oxide materials have a low piezoelectric coefficient due to their inherent potential shielding effect, which affects their actual application effect as piezoelectric materials. The glycine-polyvinyl alcohol piezoelectric film and powder used in the piezoelectric components of the hydrogel in the present invention have a higher piezoelectric coefficient than traditional organic piezoelectric materials, provide a higher piezoelectric voltage to trigger the generation of free radicals inside the molecules and the chain reaction, and the preparation method and preparation conditions are mild, and the raw materials are easy to obtain.

[0013] At the same time, the methacryloyl silk fibroin and glycine-polyvinyl alcohol components used in the colloidal components of the hydrogel in the present invention have good biocompatibility, have no obvious adverse effects on the growth and proliferation of cells in the body, and are conducive to the migration and spreading of cells during tissue repair, thereby solving the problems of insufficient upper limit of mechanical strength of materials caused by colloidal materials such as polyvinyl alcohol and chitosan used in the prior art, and the inability to carry out the mechanical enhancement process in situ in animals.

[0014] Furthermore, the mass ratio of the methacrylylated silk fibroin to glycine-polyvinyl alcohol is (10-20):1.

[0015] On the other hand, the present invention provides a method for preparing a hydrogel with dynamically enhanced mechanical properties induced by a piezoelectric effect, characterized in that it comprises the following steps:

[0016] (1) The colloidal components are dissolved in a solvent to prepare a hydrogel pre-solution; the colloidal components include any one or more of methacryloyl silk fibroin (SilMA), methacryloyl gelatin (GelMA), and acrylamide (AM).

[0017] (2) adding piezoelectric components to the hydrogel pre-solution and mixing them to prepare a hydrogel solution; the piezoelectric components include any one or more of barium titanate (BaTiO3) and glycine-polyvinyl alcohol crystals;

[0018] (3) The hydrogel solution is prepared by cross-linking.

[0019] Furthermore, the colloidal component in step (1) includes methacrylylated silk fibroin; and the piezoelectric component in step (2) includes glycine-polyvinyl alcohol powder.

[0020] In some embodiments, the pre-solution in step (1) is prepared by dissolving methacryloylated silk (SilMA) in a PBS solution to obtain a SilMA solution; then, PEG-thiol (PEG-SH) as a free radical initiator is dissolved in a photocrosslinker phenyl-2,4,6-trimethylbenzoyl lithium phosphite (LAP) under light-proof conditions to obtain a PEG-SH-LAP solution; finally, the PEG-SH-LAP solution is added to the SilMA solution, and the mixture is mixed evenly to obtain a SilMA solution containing a photocrosslinker and a free radical initiator, i.e., the pre-solution.

[0021] Preferably, the final concentration of PEG-thiol in the SilMA solution is 2% (m / v), and the final concentration of LAP in the SilMA solution is 0.2% (m / v).

[0022] In some embodiments, the piezoelectric component glycine-polyvinyl alcohol crystal powder in step (2) is formed by crushing a glycine (γ-Gly) film assisted by polyvinyl alcohol (PVA) in γ-crystal form through a ball mill to form PVA-γ-Gly powder, and then the pre-solution described in step (1) is added to the PVA-γ-Gly powder and mixed quickly and evenly.

[0023] Preferably, in the preparation process of the polyvinyl alcohol-assisted γ-crystal glycine film, the concentration of glycine and polyvinyl alcohol before mixing is 10% (m / v), and after mixing evenly, the homogeneous glycine-polyvinyl alcohol solution is spread in a culture dish to form a liquid film, and then dried in a 65°C oven for crystallization for not less than 35 minutes. The glycine-polyvinyl alcohol crystal film needs to be treated with liquid nitrogen for 10 minutes before being crushed in a ball mill. The frequency of the ball mill is set to 50 Hz, and the crushing time is set to 1 minute.

[0024] Furthermore, the final concentration of methacryloylated silk in the hydrogel solution is 10% to 30% (m / v), and the final concentration of glycine-polyvinyl alcohol powder is 1% to 3% (m / v).

[0025] Preferably, the final concentration of methacryloyl silk in the hydrogel solution is 30% (m / v), and the final concentration of glycine-polyvinyl alcohol powder is 2% (m / v).

[0026] In some embodiments, the hydrogel solution in step (3) is pre-crosslinked by ultraviolet light for 30 seconds to obtain a piezoelectric silk hydrogel with lower initial mechanical strength; the low mechanical strength piezoelectric silk hydrogel is placed on an ultrasonic therapy device probe for ultrasonic treatment to obtain a piezoelectric silk hydrogel with enhanced mechanical strength.

[0027] In another aspect, the present invention provides a method for using a hydrogel with dynamically enhanced mechanical properties induced by a piezoelectric effect, wherein the mechanical properties of the hydrogel are enhanced by subjecting the hydrogel to ultrasound, and the hydrogel is as described above.

[0028] In some methods, the piezoelectric effect is used to induce the generation of piezoelectric effect inside the hydrogel and the enhancement of the mechanical strength of the hydrogel by ultrasonic loading through various ultrasonic generating devices. The portability of ultrasonic equipment is conducive to the development of treatment. The high penetration of high-frequency ultrasound is conducive to loading the hydrogel scaffold at the level of cartilage tissue defects. At the same time, the damage and pain in the animal body caused by ultrasonic loading are relatively low. The mechanical properties of the hydrogels induced by ultrasound equipment used for physical therapy vary in the range of kPa-10 kPa. The lower limit of the kPa level of mechanical strength change is conducive to avoiding the occurrence of inflammatory reactions in the early stage of tissue repair, and the upper limit of the 10 kPa level of mechanical strength change is conducive to promoting the regeneration of osteochondral tissue. The use of non-physical therapy high-frequency focused ultrasound equipment may enable the mechanical strength of the material to reach a higher level.

[0029] Furthermore, the frequency of the ultrasound used for physical therapy is 1-5 MHz, and the sound intensity is 1-3 W / cm 2 The ultrasonic treatment time is not less than 2 hours. The frequency of high-frequency focused ultrasound used for non-physical therapy is generally 2.5-5MHz, and the sound intensity can reach 100W / cm 2 above.

[0030] Preferably, the frequency of the ultrasound used for physical therapy is 1 MHz and the sound intensity is 2.5 W / cm 2 The ultrasonic treatment time is not less than 2 h.

[0031] In some methods, during the process of piezoelectric effect-induced increase in the mechanical strength of hydrogels, the change in the mechanical strength of hydrogel materials can be regulated by applying the time, sound intensity and frequency of external ultrasonic intervention. The storage modulus of the hydrogel material is in a process of dynamic and controllable increase during ultrasonic loading, and the specific mechanical strength that the hydrogel ultimately reaches can be controlled by adjusting the ultrasonic loading time.

[0032] In some embodiments, other methods such as magnetic field can be used to induce mechanical enhancement of hydrogel through piezoelectric effect. The method of inducing mechanical enhancement can be selected according to the convenience of the specific user.

[0033] On the other hand, the present invention provides a use of a mixture for preparing a hydrogel whose mechanical properties are dynamically enhanced by piezoelectric effect induced by ultrasound, characterized in that the mixture is prepared by cross-linking a piezoelectric component and a colloidal component; the piezoelectric component includes any one or more of barium titanate and glycine-polyvinyl alcohol crystals, and the colloidal component includes any one or more of methacryloyl silk, methacryloyl gelatin, and acrylamide.

[0034] Furthermore, the piezoelectric component includes glycine-polyvinyl alcohol crystals, and the colloidal component includes methacrylylated silk.

[0035] On the other hand, the present invention provides a mixture for preparing a hydrogel with dynamically enhanced mechanical properties for improving the treatment effect of cartilage defects, wherein the mixture is prepared by cross-linking a piezoelectric component and a colloidal component; the piezoelectric component includes any one or more of barium titanate and glycine-polyvinyl alcohol crystals, and the colloidal component includes any one or more of methacryloyl silk, methacryloyl gelatin, and acrylamide.

[0036] Furthermore, the hydrogel dynamically enhances its mechanical properties by inducing piezoelectric effect through ultrasound.

[0037] It is understandable that, in addition to ultrasound used in the preferred embodiment of the present invention, other methods that utilize the piezoelectric effect principle to induce the hydrogel mechanical enhancement effect are applicable to the present invention.

[0038] In another aspect, the present invention provides a use of glycine-polyvinyl alcohol crystals for preparing a hydrogel whose mechanical properties are dynamically enhanced by an ultrasound-induced piezoelectric effect.

[0039] Glycine-polyvinyl alcohol piezoelectric films and powders have higher piezoelectric coefficients than traditional organic piezoelectric materials, providing higher piezoelectric voltages to trigger the generation of free radicals inside the molecules and the occurrence of chain reactions.

[0040] In another aspect, the present invention provides a use of methacrylylated silk fibroin for preparing a hydrogel whose mechanical properties are dynamically enhanced by an ultrasound-induced piezoelectric effect.

[0041] Methacrylylated silk has good biocompatibility and is beneficial to the migration and spreading of cells during tissue repair.

[0042] Furthermore, the hydrogel with dynamically enhanced mechanical properties is beneficial to the regeneration and repair of the osteochondral tissue in the present invention.

[0043] In some embodiments, the hydrogel with dynamically enhanced mechanical properties is also suitable for tissues with dynamic mechanical requirements during the regeneration and repair process, such as bone tissue, through formulation adjustment and selection of the method for inducing mechanical enhancement.

[0044] Compared with the prior art, the present invention has the following advantages and effects:

[0045] 1. Glycine-polyvinyl alcohol piezoelectric films and powders have higher piezoelectric coefficients than traditional organic piezoelectric materials, providing higher piezoelectric voltages to trigger free radical generation and chain reactions within the molecules. In addition, their preparation methods and conditions are mild, and the raw materials are easily available.

[0046] 2. Methacrylylated silk and glycine-polyvinyl alcohol components have good biocompatibility, have no obvious adverse effects on the growth and proliferation of cells in the body, and are conducive to the migration and spreading of cells during tissue repair;

[0047] 3. The dynamic enhancement range of the mechanical properties of piezoelectric effect hydrogels induced by therapeutic ultrasound facilities is kPa-10kPa. The lower limit of the change in mechanical strength of the order of kPa is beneficial to avoiding the occurrence of inflammatory response in the early stage of tissue repair, and the upper limit of the change in mechanical strength of the order of 10 kPa is beneficial to promoting the regeneration of osteochondral tissue; when the ultrasound equipment has a higher ultrasound frequency and ultrasound intensity, the mechanical properties may reach a higher level.

[0048] 4. In the process of increasing the mechanical strength of hydrogels through the piezoelectric effect, the change in the mechanical strength of hydrogel materials can be regulated by the time of external ultrasonic intervention. The storage modulus of hydrogel materials is in a process of dynamic and controllable increase during ultrasonic loading. By adjusting the time of ultrasonic loading, the specific mechanical strength of the hydrogel can be controlled;

[0049] 5. The piezoelectric effect inside the hydrogel and the way to enhance the mechanical strength of the hydrogel are ultrasonic loading with a handheld ultrasonic device. The portability of the ultrasonic device is conducive to the development of treatment, and the high penetration of high-frequency ultrasound is conducive to loading the hydrogel scaffold at the level of cartilage tissue defects. At the same time, the damage and pain in the animal body caused by ultrasonic loading are relatively low. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a flow chart of the preparation of the silk fibroin hydrogel provided by the present invention in Example 1;

[0051] Figure 2 The piezoelectric coefficient of the PVA-glycine piezoelectric crystal film and the cross-sectional structure of the piezoelectric hydrogel in Example 6;

[0052] Figure 3is the transient voltage generated by the piezoelectric hydrogel in Example 6 and the piezoelectric coefficient D of the material at different γ-Gly concentrations 33 ;

[0053] Figure 4 The macroscopic mechanical characteristics of the piezoelectric hydrogel under different conditions in Example 6;

[0054] Figure 5 The effect of different pre-crosslinking times on the mechanical strength of the piezoelectric hydrogel in Example 7;

[0055] Figure 6 is the specific mechanical strength of the piezoelectric hydrogel in Example 8 at different ultrasound times;

[0056] Figure 7 is the mechanical strength of the silk hydrogels with different concentration gradients in Example 9 after photocrosslinking for 30 s;

[0057] Figure 8 The mechanical strength of the piezoelectric hydrogel with 10% silk fibroin in Example 10 at different ultrasound times;

[0058] Fig. 9 The mechanical strength of the piezoelectric hydrogel with 20% silk fibroin in Example 10 at different ultrasound times;

[0059] Fig.10 The mechanical strength of the hydrogels with different PVA-γ-Gly concentrations under different ultrasound times in Example 11;

[0060] Fig.11 The mechanical strength of the GelMA piezoelectric hydrogel in Example 12 at different ultrasound times;

[0061] Fig.12 The mechanical strength of the BaTiO3-silk fibroin hydrogel in Example 13 at different ultrasound times;

[0062] Fig.13 The biocompatibility of the piezoelectric hydrogel in Example 15 and its effect on cell morphology;

[0063] Fig.14 The effect of the mechanically controllable enhanced piezoelectric hydrogel on the expression of cell chondrogenic genes in Example 16;

[0064] Fig.15 This is the effect of the mechanically controllable enhanced piezoelectric hydrogel in Example 17 on the repair of rabbit bone cartilage tissue. DETAILED DESCRIPTION

[0065] The present invention is further described in detail below in conjunction with the examples. It should be noted that the examples described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it. Unless otherwise specified, the raw materials used in the examples are all purchased commercially.

[0066] Example 1. Preparation of hydrogel provided by the present invention (30% silk fibroin, 2% PVA-γ-Gly)

[0067] (1) degumming and air-drying the mulberry silk, weighing the degummed silk and methacrylamide in a mass ratio of (1:4), dissolving the degummed silk in the methacrylamide solution by stirring to obtain a methacrylamide silk solution (SilMA), and freeze-drying the solution to form a SilMA powder;

[0068] (2) SilMA powder and PBS solution were weighed in a mass ratio of (3:10) to prepare a SilMA mixed solution, and then PEG-thiol (PEG-SH) as a free radical initiator and photocrosslinker phenyl-2,4,6-trimethylbenzoyl lithium phosphite (LAP) were weighed in a mass ratio of (1:1), and dissolved in a light-proof condition to obtain a PEG-SH-LAP solution. Then, the SilMA mixed solution and the PEG-SH-LAP solution were evenly mixed in a volume ratio of (20:1) to obtain a pre-solution;

[0069] (3) weighing and dissolving glycine (Gly) powder and distilled water in a mass-to-volume ratio of (1:10); weighing and dissolving polyvinyl alcohol (PVA) and distilled water in a mass-to-volume ratio of (1:10); and then mixing the glycine solution and the polyvinyl alcohol solution in a volume ratio of (1:1) to obtain a solution;

[0070] (4) Spreading the mixed solution obtained in step (3) in a culture dish to form a liquid film, and then drying it in an oven at 65°C for not less than 35 min to obtain a crystal film. The crystal film was treated with liquid nitrogen for 10 min and then crushed using a ball mill to obtain PVA-γ-Gly powder. The frequency of the ball mill was 50 Hz and the crushing time was 1 min.

[0071] (5) The pre-solution obtained in step (2) and PVA-γ-Gly powder were weighed at a concentration ratio of 30% (m / v): 2% (m / v), mixed quickly and evenly, and subjected to UV pre-crosslinking for 30 s to obtain a piezoelectric silk hydrogel with a relatively low initial mechanical strength;

[0072] (6) The hydrogel obtained in step (5) is placed on the probe of an ultrasonic therapy device for ultrasonic treatment. The ultrasonic frequency is 1 MHz and the sound intensity is 2.5 W / cm 2 The time required is no less than 2 h, and the piezoelectric silk hydrogel with enhanced mechanical strength is obtained. Figure 1 shown.

[0073] Example 2: Preparation of 20% silk fibroin hydrogel

[0074] The preparation steps in Example 1 were followed, wherein the concentration ratio of the pre-solution to the PVA-γ-Gly powder in step (5) was 20% (m / v): 2% (m / v), and the mixture was weighed and mixed, and ultrasonication was performed to obtain a 20% silk fibroin hydrogel.

[0075] Example 3: Preparation of 10% silk fibroin hydrogel

[0076] The preparation steps in Example 1 were followed, wherein the concentration ratio of the pre-solution to the PVA-γ-Gly powder in step (5) was 10% (m / v): 2% (m / v), and the pre-solution was weighed and mixed, and 10% silk fibroin hydrogel was obtained by ultrasonication.

[0077] Example 4: Preparation of 1% PVA-γ-Gly hydrogel

[0078] The preparation steps in Example 1 were followed, wherein the concentration ratio of the pre-solution to the PVA-γ-Gly powder in step (5) was 30% (m / v):1% (m / v), and the pre-solutions were weighed and mixed, and 1% PVA-γ-Gly hydrogel was obtained by ultrasonication.

[0079] Example 5. Preparation of 3% PVA-γ-Gly hydrogel

[0080] The preparation steps in Example 1 were followed, wherein the concentration ratio of the pre-solution to the PVA-γ-Gly powder in step (5) was 30% (m / v): 3% (m / v), and the pre-solutions were weighed and mixed, and 3% PVA-γ-Gly hydrogel was obtained by ultrasonication.

[0081] Example 6: Performance test of the hydrogel provided by the present invention

[0082] The hydrogel prepared in Example 1 was analyzed for physical and chemical properties by elemental energy spectrum analysis, scanning electron microscope observation and compression elastic modulus testing machine, macroscopic electrical performance analysis was performed by electrochemical workstation, and macroscopic mechanical performance analysis was performed by rheometer testing method.

[0083] 1. Physical and chemical properties

[0084] Depend on Figure 2 It can be seen that the synthesized glycine-polyvinyl alcohol is γ-crystalline glycine with strong piezoelectric properties, and the cross-linking degree of the silk hydrogel with piezoelectric effect is improved after ultrasonic loading.

[0085] (II) Macroscopic electrical properties

[0086] Depend on Figure 3It can be seen that the piezoelectric properties of the hydrogel doped with γ-crystalline glycine are significantly improved, and the transient voltage generated under ultrasound conditions reaches 0.16 V, indicating that the piezoelectric material γ-Gly can significantly improve the piezoelectric properties of the hydrogel. 33 Afterwards, Figure 3 As shown in the figure, we found that the piezoelectric coefficient of 0.5% γ-Gly was only 0.62pm / V. At 1% and 2% glycine concentrations, the piezoelectric coefficient of the material reached 1.68pm / V and 3.52pm / V, respectively, and reached 3.84pm / V at a higher 4% γ-Gly concentration. This further verifies that γ-glycine can significantly improve the piezoelectric properties of hydrogels. Considering that the piezoelectric coefficient increases slowly at concentrations above 2% γ-Gly, 2% polyvinyl alcohol-assisted γ-crystalline glycine, i.e. glycine-polyvinyl alcohol, was finally selected for subsequent experiments.

[0087] (III) Macroscopic mechanical properties

[0088] Depend on Figure 4 It can be seen that the compression modulus of piezoelectric silk hydrogel increases with the extension of ultrasound time. After ultrasound treatment, the compression resistance is stable, the swelling rate decreases, and the macroscopic mechanical strength shows an upward trend. The range of mechanical property change is kPa-10 kPa. The lower limit of the mechanical strength change of kPa is beneficial to avoid the occurrence of inflammatory response in the early stage of tissue repair, and the upper limit of the mechanical strength change of 10 kPa is beneficial to promote the regeneration of osteochondral tissue.

[0089] Example 7: Changes in mechanical strength of hydrogel at different pre-crosslinking times

[0090] According to the hydrogel preparation steps provided in Example 1, the pre-crosslinking time was set to 15 s, 30 s, 45 s and 60 s, and hydrogels with different pre-crosslinking times were prepared. The mechanical properties of the hydrogels under different pre-crosslinking conditions were analyzed, and the test results are shown in Tables 1 and Figure 5 , where the storage modulus G' and loss modulus G" represent the stiffness and state of the material, respectively.

[0091] Table 1 Effect of different pre-crosslinking times on the mechanical strength of hydrogels

[0092]

[0093] According to the results, the storage modulus increases with the extension of the pre-crosslinking time. In order to keep the initial mechanical strength of the hydrogel at a low level after pre-crosslinking so as to adapt to the initial inflammatory response period of cartilage tissue defects, the pre-crosslinking time used in the present invention is 30 s.

[0094] Example 8: Changes in mechanical properties of hydrogels at different ultrasound times

[0095] The hydrogels prepared in Example 1 were subjected to ultrasonic treatment for different lengths of time, wherein the controls were the lack of piezoelectric material and no ultrasonic loading, no ultrasonic loading, and the lack of piezoelectric material and only ultrasonic loading (2 h). The mechanical properties of the hydrogels under different ultrasonic conditions were then analyzed. The test results are shown in Tables 2 and Figure 6 .

[0096] Table 2 Effects of different ultrasound times on the mechanical properties of hydrogels

[0097]

[0098] According to the above results, there is no significant change in the mechanical properties of hydrogels without ultrasonic loading or with ultrasonic loading only in the absence of piezoelectric materials; the mechanical properties of silk hydrogels significantly improve with the extension of ultrasonic loading time, and finally reach a storage modulus of more than 10kPa.

[0099] Example 9 Mechanical strength of hydrogels with different SilMA concentrations at a pre-crosslinking time of 30 s

[0100] According to the hydrogel preparation steps provided in Examples 2 and 3, hydrogels with different SilMA concentrations were prepared, wherein the PVA-γ-Gly concentration was 2%. The mechanical properties were then tested, and the test results are shown in Figure 7 .

[0101] By comparing Examples 7 and 9, it can be seen that when the silk fibroin concentration of the hydrogel is low (10%, 20%), its mechanical properties are less affected by the photocrosslinking time, and the mechanical properties are less than the kPa level under short-time pre-crosslinking; when the silk fibroin concentration of the hydrogel is 30%, the storage modulus can reach 2 kPa when the crosslinking time reaches 30 s, so the preferred silk fibroin concentration of the present invention is 30%.

[0102] Example 10 Mechanical strength of hydrogels with different SilMA concentrations at different ultrasound times

[0103] According to the method of Example 2 and Example 3, hydrogels with different SilMA concentrations were prepared, wherein the ultrasound time was set to 0 h, 1 h, and 2 h, and then mechanical properties were tested respectively. The test results are shown in Table 3. Figure 8 and Fig. 9 .

[0104] Table 3 Effect of different ultrasound times on the mechanical strength of hydrogels with different SilMA concentrations

[0105]

[0106] By comparing Example 8 and Example 10, it can be seen that when the silk concentration is low (10%), the effect of improving the mechanical strength of the hydrogel under the influence of ultrasound is not obvious; when the silk concentration is 20%, the mechanical strength of the hydrogel is improved under the influence of ultrasound, but the value that can be achieved is limited (1500 Pa); when the silk concentration is 30%, the hydrogel can reach a storage modulus of more than 10 kPa, so the present invention preferably uses a combination of 30% silk concentration and 2 h of ultrasound to prepare hydrogel.

[0107] Example 11 Mechanical strength of hydrogels with different PVA-γ-Gly concentrations at different ultrasound times

[0108] According to the methods of Examples 4 and 5, hydrogels with different PVA-γ-Gly concentrations were prepared, wherein the ultrasonic time was set to 0 h, 1 h, and 2 h, and then mechanical properties were tested respectively. The test results are shown in Tables 4 and Fig.10 .

[0109] Table 4 Effect of different ultrasound times on the mechanical strength of PVA-γ-Gly hydrogels with different concentrations

[0110]

[0111] By comparing Examples 8 and 11, it can be seen that when the glycine-polyvinyl alcohol concentration of the hydrogel is 1%, the mechanical strength of the hydrogel gradually increases with the extension of the ultrasonic loading time, and the storage modulus finally reaches 8 kPa; when the glycine-polyvinyl alcohol concentration of the hydrogel is 2%, the mechanical properties of the hydrogel are significantly improved with the extension of the ultrasonic loading time, and finally reach a storage modulus of more than 10 kPa; when the glycine-polyvinyl alcohol concentration of the hydrogel is 3%, the storage modulus of the hydrogel is not significantly improved compared with the mechanical strength of the hydrogel with a glycine-polyvinyl alcohol concentration of 2% under the same ultrasonic conditions. Therefore, the preferred glycine-polyvinyl alcohol concentration of the present invention is 2%, and the ultrasonic time is 2h.

[0112] Example 12: Effects of different colloid components on the preparation of piezoelectric hydrogels with dynamically enhanced mechanical properties

[0113] According to the hydrogel preparation steps provided in Example 1, the colloid components are replaced with acrylamide gel (AM) and methacryloyl gelatin (GelMA), and then the physical and chemical properties and mechanical properties of the hydrogel are tested and analyzed. The test results show that the mechanical strength of the 20% (m / v) piezoelectric-acrylamide hydrogel increases from 2kPa to 4kPa as the ultrasonic time (0~2h) increases. For the piezoelectric-methacryloyl gelatin (GelMA) hydrogel, its solubility properties are comprehensively considered and finally a 10% (m / v) concentration of GelMA is used to test its mechanical properties. The results show that as the ultrasonic time increases, the mechanical properties of the piezoelectric-methacryloyl gelatin hydrogel increase from 2kPa to 3kPa, and the mechanical enhancement effect is quite obvious at 1h (such as Fig.11 as shown).

[0114] Compared with the results of Example 6, it can be seen that after the methacrylylated silk in the hydrogel colloidal constituents is replaced with acrylamide gel (AM) and methacrylylated gelatin (GelMA), the crosslinking degree and mechanical strength of the hydrogel are improved, but the storage modulus of the two hydrogels can only reach 3-4kPa, which is not as good as the hydrogel provided by the present invention. The hydrogel provided by the present invention can finally reach a mechanical strength of more than 10kPa after ultrasonic loading, which is more conducive to the regeneration of cartilage tissue. In addition, the colloidal constituents provided by the present invention are more effective in promoting the repair of osteochondral tissue. It may be due to the principle that the piezoelectric effect enhances the mechanical properties by inducing free radicals to attack the carbon-carbon double bonds of the hydrogel molecules. Therefore, the hydrogel monomer that can be enhanced by the piezoelectric effect can be other biocompatible molecules that modify the carbon-carbon double bonds.

[0115] Example 13: Effects of different piezoelectric components on the preparation of piezoelectric hydrogels with dynamically enhanced mechanical properties

[0116] According to the hydrogel preparation steps provided in Example 1, the piezoelectric component was replaced with barium titanate (BaTiO3) and the physical and chemical properties and mechanical properties of the hydrogel were tested and analyzed. The test results are shown in Fig.12 .

[0117] Comparative Examples 6 and 13 show that when the piezoelectric constituent is barium titanate, the crosslinking degree and mechanical strength of the hydrogel are also improved under ultrasonic loading. Since the vector sum of the electric dipole moment of amino acid crystals tends to offset each other under natural crystallization conditions, and can produce a strong polarization intensity under specific crystallization conditions, the gamma-crystalline glycine in the composition can be replaced by other amino acid crystals or piezoelectric materials with piezoelectric effect crystal forms. However, the mechanical strength of the hydrogel prepared from barium titanate can only reach a storage modulus of 6 kPa, which cannot meet the 10 kPa storage modulus that is conducive to promoting the regeneration of osteochondral tissue, and the effect is not as good as the hydrogel provided by the present invention. Therefore, the piezoelectric constituent provided by the present invention is more effective in promoting the repair of osteochondral tissue.

[0118] Example 14: Effects of different loading methods for inducing piezoelectric effect on the preparation of piezoelectric hydrogels with dynamically enhanced mechanical properties

[0119] According to the hydrogel preparation steps provided in Example 1, the ultrasonic loading method is replaced by external mechanical loading, and then the physicochemical properties and mechanical properties of the hydrogel are tested and analyzed. When a stress of 50 N is applied for loading, the mechanical properties of the hydrogel are gradually enhanced from 1 kPa to 4 kPa. Comparative Examples 6 and 14 show that the cross-linking degree and mechanical strength of the hydrogel can also be improved by using external mechanical loading, because the loading method that causes the change of the molecular dipole moment of the piezoelectric material inside the hydrogel molecule can also cause the free radical chain reaction inside the hydrogel to be carried out, thereby causing the mechanical strength of the hydrogel to increase, but the storage modulus of the hydrogel can only reach 4 kPa by using external mechanical loading, which cannot meet the 10 kPa storage modulus that is conducive to promoting the regeneration of osteochondral tissue. Therefore, the loading method that induces the piezoelectric effect provided by the present invention is more effective in promoting the repair of osteochondral tissue and in actual medical treatment.

[0120] Example 15: Study on biocompatibility of hydrogel

[0121] The hydrogel prepared in Example 1 was treated with piezoelectric material (SFG) and piezoelectric material ultrasonic treatment (SFGP) at the same time, and the control was treated with a well plate without material. After 1 D, 3 D, and 5 D of treatment, the absorbance of the hydrogel at a wavelength of 450 nm was measured by a microplate reader using a CCK-8 kit detection method, and the changes in the cell attachment state on hydrogel materials with different hardness were analyzed by scanning electron microscopy.

[0122] like Fig.13As shown in the figure, compared with the control, there was no significant difference in the biocompatibility results of the SFG group and the SFGP group, and the absorbance increased significantly in 3D, indicating that the piezoelectric material had no significant harm to the proliferation of cells; it can be seen that the hydrogel material provided by the present invention has good biocompatibility and has no obvious effect on the growth and proliferation of cells. At the same time, the mechanically enhanced piezoelectric hydrogel is conducive to the spreading and attachment of cells.

[0123] Example 16: Upregulation of chondrogenic gene expression by enhanced hydrogel mechanical properties

[0124] In order to further illustrate the specific effect of hydrogel in cartilage repair, qPCR technology was used to measure the gene expression of cells cultured on the surface of hydrogel without ultrasound loading and hydrogel after ultrasound loading under 7-day and 14-day chondrogenic induction experimental conditions, where the control group was cells cultured on the well plate without material. The measurement results are shown in Fig.14 .

[0125] According to the results, under the 7-day experimental conditions, the expression levels of chondrogenic genes COL-2A1 and ACAN in the cultured cells treated with ultrasonic loading were significantly upregulated, and there was no significant difference in the expression of SOX9 gene. Under the 14-day experimental conditions, the expression levels of COL-2A1, SOX9, and ACAN in the cultured cells treated with ultrasonic loading were significantly increased, indicating that the hydrogel material after ultrasonic loading treatment can promote the expression of chondrogenic genes and contribute to the repair of osteochondral tissue.

[0126] Example 17: Repair of rabbit cartilage tissue by enhancing the mechanical properties of hydrogel

[0127] In order to illustrate the specific effect of mechanically enhanced hydrogel in the application of cartilage repair in vivo, the rabbit femoral cartilage defect model was used to verify the repair time points of 4 weeks and 8 weeks, with or without ultrasound-induced material mechanical enhancement. The control group only performed cartilage defect modeling; the experimental groups were piezoelectric hydrogel without ultrasound enhancement treatment and piezoelectric hydrogel with ultrasound enhancement treatment.

[0128] like Fig.15 As shown in the figure, at 4 weeks and 8 weeks, the repair effect of ultrasound-loaded mechanically enhanced hydrogel on rabbit femoral cartilage defects was significantly better than that of the experimental group without ultrasound enhancement and the defect control group, indicating that ultrasound-induced mechanical enhancement of piezoelectric hydrogel is beneficial to the regeneration of cartilage tissue.

[0129] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A hydrogel with dynamically enhanced mechanical properties induced by piezoelectric effect, characterized in that: The hydrogel comprises piezoelectric components and colloidal components, and is prepared by cross-linking; the piezoelectric components comprise any one or more of barium titanate and glycine-polyvinyl alcohol crystals, and the colloidal components comprise any one or more of methacrylylated silk, methacrylylated gelatin, and acrylamide.

2. The hydrogel according to claim 1, characterized in that The piezoelectric component includes glycine-polyvinyl alcohol crystals, and the colloidal component includes methacrylylated silk.

3. The hydrogel according to claim 2, characterized in that The mass ratio of the methacrylylated silk fibroin to glycine-polyvinyl alcohol is (10-20):

1.

4. A method for preparing a hydrogel with dynamically enhanced mechanical properties induced by piezoelectric effect, characterized in that: The following steps are involved: (1) dissolving colloidal components in a solvent to prepare a hydrogel pre-solution; the colloidal components include any one or more of methacryloylated silk fibroin, methacryloylated gelatin, and acrylamide; (2) adding piezoelectric components to the hydrogel pre-solution and mixing them to prepare a hydrogel solution; the piezoelectric components include any one or more of barium titanate and glycine-polyvinyl alcohol crystals; (3) The hydrogel solution is prepared by cross-linking.

5. The preparation method according to claim 4, characterized in that: The colloidal component in step (1) includes methacryloylated silk; the piezoelectric component in step (2) includes glycine-polyvinyl alcohol powder; and the concentration of methacryloylated silk in the hydrogel solution in step (3) is 10% to 30% (m / v), and the concentration of glycine-polyvinyl alcohol powder is 1% to 3% (m / v).

6. A method for using a hydrogel with dynamic mechanical property enhancement induced by piezoelectric effect, characterized in that: By subjecting the hydrogel according to any one of claims 1 to 3 to ultrasound, its mechanical properties are enhanced.

7. The method of use according to claim 6, characterized in that: The ultrasonic frequency is 1~3 MHz, and the sound intensity is 1~2.5 W / cm 2 The ultrasonic treatment time is not less than 2 h.

8. Use of a mixture for preparing a hydrogel whose mechanical properties are dynamically enhanced by piezoelectric effect induced by ultrasound, characterized in that: The mixture is made by cross-linking a piezoelectric component and a colloidal component; the piezoelectric component includes any one or more of barium titanate and glycine-polyvinyl alcohol crystals, and the colloidal component includes any one or more of methacrylylated silk, methacrylylated gelatin, and acrylamide.

9. Use of a mixture for preparing a hydrogel with dynamic mechanical properties for improving the treatment effect of cartilage defects, characterized in that: The mixture is made by cross-linking a piezoelectric component and a colloidal component; the piezoelectric component includes any one or more of barium titanate and glycine-polyvinyl alcohol crystals, and the colloidal component includes any one or more of methacrylylated silk, methacrylylated gelatin, and acrylamide.

10. The use according to claim 9, characterized in that The hydrogel dynamically enhances its mechanical properties by inducing piezoelectric effect through ultrasound.

Citation Information

Patent Citations

  • Preparation method of artificial load-bearing hydrogel for cartilage

    CN105963793A

  • Hydrogel microneedle patch loaded with bionic enzyme and preparation method

    CN118304457A

  • Electro-mechanical coupling hydrogel microsphere with stable mechanical property and low loss transduction as well as preparation method and application of electro-mechanical coupling hydrogel microsphere

    CN119661873A

  • Multi-drive composite double-response gel system and preparation method thereof

    CN119684640A

  • Treatment method of heavy metal-containing liquid

    JP2007319851A

Cited By

  • Piezoelectric hydrogel performance optimization method based on deep learning

    CN121034490A

  • Double-layer hydrogel stent for realizing articular cartilage injury repair through ultrasonic regulation and control as well as preparation method and application of double-layer hydrogel stent

    CN121534230A